Peran Apresiasi Orang Tua Dalam Proses Pendidikan Anak di Rumah untuk Membangun Sikap Percaya Diri di Kalangan Siswa Kelas VIII SMPN 1 Bogor - Ali Hadiyanto; Ismy Aisyahi; Reni Sinta Dewi (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Self-confidence is a very important aspect, especially in the student learning process, with confidence there will be a process of change in students not only in learning outcomes but also in student behavior and attitudes, namely courage, activeness, and student self-actualization during the teaching and learning process. Building a confident attitude needs to be supported by several things, especially the family environment (parents). This study describes how the role of parents in giving appreciation to foster self-confidence in children in home education. This study aims to determine how the role of parental appreciation in building children's self-confidence and what factors hinder and support efforts to build children's self-confidence. This research uses descriptive qualitative methods. The data was validated using the data source triangulation technique (combined observation, interview, and documentation). The sources and informants in this study are teachers, students, and parents of students. The results stated that parental appreciation acts as a motivation for children to be enthusiastic about learning, as an increase in children's creativity, and as an increase in children's independence. Factors that act as supporters and inhibitors are, cooperation between parents and children, mutual openness and understanding between parents and children, parents’ educational background, economic background, environment, free time that parents provide, parents' busyness, and fulfillment of children's needs by parents. Keywords: Parental appreciation; Education; Confident attitude